2013
DOI: 10.5812/cardiovascmed.10686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Severe Tricuspid Regurgitation on Long Term Survival

Abstract: Background:Tricuspid regurgitation (TR) is a common echocardiographic finding, which often accompanies left sided valve disease. Data on mortality and morbidity in patients with severe TR are limited.Objectives:We sought to assess the outcome of patients with severe TR with the hypothesis that significant TR adversely impacts quality of life and survival, independent of pulmonary artery pressure (PAP) and left ventricular ejection fraction (LVEF).Materials and Methods:Between 2002 and 2012, 358 consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 19 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…Several more recent studies confirmed these results and therefore underlined the correlation between severity of TR and increased mortality ( 25–29 ). In addition, patients with severe symptomatic TR showed prolonged hospitalization and a higher rate of rehospitalization ( 26 ).…”
Section: Epidemiology and Prognostic Impact Of Trmentioning
confidence: 99%
“…Several more recent studies confirmed these results and therefore underlined the correlation between severity of TR and increased mortality ( 25–29 ). In addition, patients with severe symptomatic TR showed prolonged hospitalization and a higher rate of rehospitalization ( 26 ).…”
Section: Epidemiology and Prognostic Impact Of Trmentioning
confidence: 99%
“…Patients affected by tricuspid regurgitation present with the following symptoms: fatigue, atrial fibrillation, discomfort especially in the neck region, ascites, liver and renal dysfunction, abdominal discomfort and pain, sleeplessness, swelling in the lower limbs, cardiac activities in the veins of the lower limbs, pleural or cardiac effusion, shortness of breath, and cold skin. These symptoms are most commonly associated with severe heart disease ( 3 ) . The diagnosis of tricuspid valve disease can be facilitated by using electrocardiogram (ECG), Doppler echocardiography, magnetic resonance imaging (MRI), radionuclide scan, chest X-ray, transesophageal echocardiography, and cardiac catheterization ( 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately 1.6 million patients with TR in the US alone [1][2][3]. Higher risk of mortality and morbidity, and higher rates of hospitalization are reported as consequences of severe TR if untreated [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%